MENINGKATKAN MINAT WIRAUSAHA MELALUI PELATIHAN POT BUNGA DARI SERABUT KELAPA PADA IBU-IBU PKK DESA LANCANG KUNING - Yanto, Meidi; Komalasari, Annisa Dwi Fitri; Utomo, Cahyani; Sanjaya, Putra Octory; Robiyansyah, Robiyansyah; Nurdiyaningsih, Teki (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2025)
In Lancang Kuning Village, there is one resident who manages coconut plants which are processed into plant fertilizer, where the part used as fertilizer is the coconut shell so that the remaining fibers are not used. Therefore, KKN students in Lancang Kuning Village have the initiative to process leftover coconut materials to make coconut fiber crafts. Where this craft is carried out through training so that this activity can provide education and entrepreneurial interest in the Lancang Kuning village community in utilizing leftover materials. Training on Flower Pot Crafts from Coconut Fiber was held on Friday 03 November 2023 at the Lancang Kuning Village Hall with the training participant, Mrs. PKK, Lancang Kuning Village. During the training, the entire team was able to work together well and provided equipment to support the progress of the Training on Making Flower Pots from Coconut Fibe